Kantin Kejujuran Sebagai Media Pembelajaran Pengembangan Nilai Karakter Jujur Pada Anak Usia Dini di Tk Bakti Persada: Penelitian - Widariyati; Farida Nur Kumala; Henni Anggraini (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Character is a quality that reflects a person's moral and ethical habits, which are manifested through thoughts, feelings, and actions. Honesty is one of the main values in character education, so it needs to be instilled in children from an early age. The development of character values in children can be done with various methods that are fun for children. This study aims to determine how the honesty canteen is a learning medium for developing honest character values in early childhood. This study uses a qualitative method with a descriptive format. Researchers are the main instrument in collecting data using observation guides based on indicators mentioned by the Directorate General of Non-Formal and Informal Early Childhood Education in 2012 as well as interviews with school principals, educators or teachers and parents. From the results of the study it can be concluded that the honesty canteen can be used as a learning medium for developing honest character values that are effective and innovative in early childhood.